PENGARUH EFIKASI DIRI MOTIVASI KERJA DAN DISPLIN KERJA TERHADAP KOMITMEN ORGANISAIONAL PADA SATAFF CV. ISTANA MIE DAN ES SEMARANG - Suristiyani, 13.05.51.0126 (Students' Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of self-efficacy, motivation and discipline to organizational commitment in the staff CV. Mie dan Es Semarang. The population in this study were all staff CV. Mie dan Es Semarang which amounted to 102 people. All the members here will be sampled or so-called saturation sampling / census. So the sample size in this study as many as 102 people. The results of this research is the influence of self-efficacy, motivation and discipline to organizational commitment in the staff CV. Mie dan Es Semarang. Keywords: self-efficacy, motivation, work discipline and oganizational commitment